Research on digital image encryption algorithm based on double logistic chaotic map - Pan, Hailan; Lei, Yongmei; Jian, Chen (EURASIP journal on image and video processing, 2018)
With the development of information technology, image information has become the main content of network information transmission. With the development of image encryption technology, it is also about the development of image information theft technology. In order to cope with the evolving information theft technology, we must seek a better image encryption algorithm. Among many algorithms, due to the superiority of chaos technology, when the image is encrypted with chaos technology, the ciphertext presents a randomness, which makes the possibility of deciphering greatly reduced. Therefore, the research of digital image encryption algorithm based on chaos technology has become an important means of modern digital image encryption. In this paper, the digital image encryption technology is studied with the dual logistic chaotic map as a tool. The simulation experiments are carried out by using the classical Lena image and the life picture, and the results are analyzed from the histogram, pixel correlation, information entropy, key space size, key sensitivity, and so on. The results show that the method used in this paper has a better security effect.